Student-delivered behavior-specific praise: a systematic literature review and meta-analysis - Royer, David James; Ennis, Robin Parks (Frontiers in Education, 2024)
Behavior-specific praise is an easy to implement teacher-delivered strategy that supports academic engagement while preventing and reducing disruptive behavior. By letting students know what they did, specifically, to meet academic, behavior, and/or social expectations, students who find teacher attention reinforcing are more likely to engage in the same behavior more often in the future. While teacher-delivered behavior-specific praise was classified as a potentially evidence-based practice using Council for Exceptional Children (2014) standards, less is known about the effects of students who deliver behavior-specific praise to their peers. This systematic literature review and meta-analysis explored the literature base and found 36 articles meeting inclusion criteria. Fifteen articles included positive peer reporting as the independent variable, 20 included tootling as the intervention, two compared those interventions, and three used an "other" form of peer praise (i.e., peer praise notes, peer monitor tokens). Nine tootling articles met all eight quality indicators by absolute coding and 32 out of all 36 studies met an 80% weighted quality indicator coding criterion for being methodologically sound. From these, we classified positive peer reporting in the mixed evidence category and tootling in the evidence-based practice category. We discuss benefits of various components in each type of peer praise intervention, limitations to the literature review, and make recommendations for future researchers.